2006
DOI: 10.2478/s11756-006-0012-1
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric ozone-induced structural changes in leaf mesophyll cell walls in grapevine plants

Abstract: Abstract:The structural changes in leaves of grapevine plants (Vitis vinifera L.) exposed to different ozone concentrations were investigated. Ozone fumigations were performed in open-top chambers at four different ozone levels (charcoal-filtered air (F), ambient air (N), ambient air + 25 mm 3 m −3 ozone (O-25) and ambient air + 50 mm 3 m −3 ozone (O-50)). The leaves of plants from chambers with increased ozone concentrations (O-25 and O-50) were significantly thicker than the controls (F), owing to increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Generally, O 3 enters into the intercellular spaces through stomata and reacts with components of the cell wall and/or cell membrane from stomata to the mesophyll regions and decomposes . However, the precise concentration of O 3 , required for reaction with cell wall and cell membrane components, is not particularly known but 1/5 or 1/10th of external concentration might be enough or is suggested to be enough .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, O 3 enters into the intercellular spaces through stomata and reacts with components of the cell wall and/or cell membrane from stomata to the mesophyll regions and decomposes . However, the precise concentration of O 3 , required for reaction with cell wall and cell membrane components, is not particularly known but 1/5 or 1/10th of external concentration might be enough or is suggested to be enough .…”
Section: Resultsmentioning
confidence: 99%
“…62 Generally, O 3 enters into the intercellular spaces through stomata and reacts with components of the cell wall and/or cell membrane from stomata to the mesophyll regions and decomposes. 63 However, the precise concentration of O 3 , required for reaction with cell wall and cell membrane components, is not particularly known but 1/5 or 1/10th of external concentration might be enough or is suggested to be enough. 64 Byvoet et al (1995) showed that at the intercellular spaces in an aqueous environment, O 3 generated O 2 -, hydroxyl radical, peroxyl radical and H 2 O 2 exposing the cellular system to higher oxidative stress.…”
Section: Wheat Plants Showed Reduced Photosynthetic Efficiency and In...mentioning
confidence: 99%
“…In terms of leaf visible injury, grapevine is regarded as sensitive to O 3 [ 8 ; 12 , 13 ]. Damage caused by O 3 on grapevine leaves includes structural changes in the cuticle and anatomical modifications at the mesophyll level inducing necrotic spots [ 14 – 15 ]. Since grapevine is a multi-annual crop, studies on its interaction with O 3 should consider the possible long-term effects on carbohydrate metabolism, allocation of resources, and grape production.…”
Section: Introductionmentioning
confidence: 99%
“…, because of its phytotoxicity as well as concentration in the troposphere, which has increased considerably during the past 60 years (Ljubesic and Britvec 2006). Peak O 3 concentrations and also emissions of ozone precursors are decreasing in Europe and North America (Ashmore 2005), but are increasing and are predicted to rise in Asia due to increased economic growth and higher emission levels of volatile organic compounds (VOCs) and nitrogen oxides (NOx; Wang et al 2005;Ohara et al 2007).…”
mentioning
confidence: 98%
“…Adverse impacts of O 3 on physiological characteristics (Biswas et al 2008) such as reductions in photosynthetic rate (Bortier et al 2001;Singh et al 2009), stomatal conductance (Guidi et al 2002), photosynthetic pigments and biochemical characteristics such as alteration in metabolic functions and enzyme activities (Calatayud and Barreno 2001;Heath 2008) are reported. Ozone is highly reactive and interacts with components of the cells from stomata to mesophyll regions (Ljubesic and Britvec 2006), O 3 , a very strong oxidant converts into reactive oxygen species (ROS) such as superoxide anion (O 2 •− ), hydroxyl radical, and hydrogen peroxide (H 2 O 2 ) in intercellular leaf spaces (apoplast) after entering through stomata (Mehlhorn et al 1990). ROS react with membrane lipids to generate lipid peroxides, which may further produce many damaging reactive oxygen intermediates through a series of reactions (Sharma and Davis 1997).…”
mentioning
confidence: 99%